Anti-TNF biosimilars in psoriasis: from scientific evidence to real-world experience. (16th November 2020) - Barker, Jonathan; Girolomoni, Giampiero; Egeberg, Alexander; Goncalves, Joao; Pieper, Burkhard; Kang, Taegyun
Abstract: Tumor necrosis factor (TNF) inhibitors account for a large proportion of drugs used to treat psoriasis and are indicated first-line options in certain settings. Several biosimilar drugs based on the anti-TNF agents adalimumab, infliximab, and etanercept are now available for use in patients with psoriasis. The favorable cost differential of biosimilars is expected to improve access to biologic therapy for biologic-naive psoriasis patients, who are often undertreated. Also, substantial cost savings can be made if patients are switched to biosimilars. To date, most clinical testing of anti-TNF biosimilars approved for use in psoriasis has been performed in patients with rheumatoid arthritis, and the results extrapolated to psoriasis. Although this may initially raise concerns for clinicians looking to start their psoriasis patients on biologic treatment with a biosimilar or switch from an original biologic to a biosimilar, the process of extrapolation is tightly regulated and scientifically justified. Furthermore, available real-world evidence of the safety and efficacy of anti-TNF agents in patients with psoriasis complements clinical trial data in patients with rheumatoid arthritis. When equipped with the appropriate knowledge, clinicians should have confidence to use biosimilars for the treatment of psoriasis.